KAJIAN KRIMINOLOGI ATAS PELECEHAN SEKSUAL TERHADAP SANTRI YANG DILAKUKAN PEKERJA DAYAH (Studi di Kabupaten Lhokseumawe) - Zainuddin, Zainuddin; Darmawan, Ridho (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
Talks about santri or children (in this case, boys) and their protection will never stop throughout the history of life, because children are the next generation to come. Sexual violence against children will have a long impact, besides having an impact on health problems in the future, it is also associated with prolonged trauma. One of the cases of sexual harassment that the author examined was sexual harassment by dayah workers against students / children. The purpose of this study was to determine the factors that led to sexual harassment by dayah workers against students, the modus operandi of dayah workers who sexually harassed students, and the countermeasures that were taken to prevent sexual harassment against students in the Daya environment. The type of research used is juridical empirical research with a case approach, which is supported by interview data and library data, and in this case the data is processed using qualitative analysis.Based on the results of the study, the factors that cause sexual harassment by dayah workers against child students include economic factors, educational level factors, social media factors, as well as family and community conditions. The modus operandi used by dayah workers is by approaching the students by offering something such as promising something to the students, the perpetrator giving a drink where the drink has been mixed with drugs that make the students sleep or fainting, the perpetrator who has a soul close to the students, the perpetrator commits violence and threats of violence against students. Countermeasures that are taken to prevent sexual harassment against santri in the dayah environment, namely the police appealing to mothers to supervise their children, conducting intensive supervision in areas deemed prone to crime, conducting routine patrols, conducting legal counseling. As well as there are preventive efforts made by individual santri, one of which is not providing opportunities or space for everyone to commit crimes of sexual harassment against them, then there are also efforts made by the community by holding a gathering between members of the community which is filled with lectures. , as well as efforts made by the Lhoksuemawe City Government by providing legal counseling and religious counseling.